Investigating teaching strategies used by teachers to foster environmental learning in the Namibian Life Science curriculum - Hoabes, Rosina (Rhodes University, Faculty of Education, Department of Education, 2004)
This study was carried out to investigate the strategies used by teachers to foster environmental learning in the Namibian Life Science curriculum in four schools in Swakopmund, Erongo Education Region. This study is a qualitative case study. I used semi-structured interviews, observation and document analysis as instruments to collect data. Two schools were selected to participate in the case study. Research participants included four teachers (two teachers from each school) of which two teachers are teaching at each school. The study was contextualised through a review of policy changes in Namibian education, which focus on learner-centred education. The study identified six strategies used by teachers to foster environmental learning in the Life Sciences curriculum. These are planning; working with information; practical, excursions and clubs; involving the learners; using visual aids and teaching materials; and choosing topics with a local focus. Through a consideration of the different strategies used by teachers, in relation to the learner-centred nature of the educational reform project in Namibia the study provides insight into the way in which teachers view learner-centred education. The study also illuminates how strategies used by teachers reflect learner-centred education principles and it outlines a number of tensions emerging in the fostering of environmental learning in learner-centred ways. The study identifies further support required by teachers, and makes recommendations which will further enhance the strategies used by teachers to foster the environmental learning focus in Life Sciences, and also enhance learner-centred teaching in Life Science.
Keywords: Life sciences -- Study and teaching -- Namibia; Education -- Namibia; Teaching -- Namibia; Effective teaching -- Namibia; Curriculum planning -- Namibia; Educational change -- Namibia; Environmental education -- Namibia